2020
DOI: 10.1128/iai.00960-19
|View full text |Cite
|
Sign up to set email alerts
|

Aging Dampens the Intestinal Innate Immune Response during Severe Clostridioides difficile Infection and Is Associated with Altered Cytokine Levels and Granulocyte Mobilization

Abstract: Clostridioides (formerly Clostridium) difficile is the most common cause of hospital-acquired infection, and advanced age is a risk factor for C. difficile infection. Disruption of the intestinal microbiota and immune responses contribute to host susceptibility and severity of C. difficile infection. However, the specific impact of aging on immune responses during C. difficile infection remains to be well described. This study explores the effect of age on cellular and cytokine immune responses during C. diffi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…The lower rate of C. difficile colonization in IBD we observed suggests that intestinal inflammation may stochastically shape the gut microbiota may be stochastic, whereas alterations in gut microbiota following antibiotic treatment is more predictable, given the specificity of these drugs. We have previously shown that in the setting of advanced age, representing a distinct immune-and microbiota-altered host state that increases risk for C. difficile infection, CDI results in age-related alterations in neutrophil and eosinophil responses in mice (25). While we found no significant difference in neutrophil responses in mice with IBD-induced or antibiotic-induced CDI, IBD was associated with differences in eosinophil response compared to CDI following antibiotic use.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…The lower rate of C. difficile colonization in IBD we observed suggests that intestinal inflammation may stochastically shape the gut microbiota may be stochastic, whereas alterations in gut microbiota following antibiotic treatment is more predictable, given the specificity of these drugs. We have previously shown that in the setting of advanced age, representing a distinct immune-and microbiota-altered host state that increases risk for C. difficile infection, CDI results in age-related alterations in neutrophil and eosinophil responses in mice (25). While we found no significant difference in neutrophil responses in mice with IBD-induced or antibiotic-induced CDI, IBD was associated with differences in eosinophil response compared to CDI following antibiotic use.…”
Section: Discussioncontrasting
confidence: 68%
“…To determine a correct dose of C. difficile spores per challenge, viable spores in each inoculum were enumerated by plating for colony-forming units (CFU) per mL on pre-reduced taurocholate cycloserine cefoxitin fructose agar (TCCFA). TCCFA was prepared as previously described (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One method would be to utilize gnotobiotic mice that do not possess a normal microbiome, 16 while another method would be to utilize antibiotics to disrupt the normal intestinal microbiome. 17–20 Different antibiotic regimens (combination antibiotic cocktail, 17–19 and cefoperazone 20 ) were utilized in different models, while the age of the mice also differed from model to model. In this paper, we reviewed the features of each animal model and the key findings from the studies.…”
Section: Aging and CDImentioning
confidence: 99%
“… 31 Abernathy-Close et al utilized aged mice that were the oldest among the published studies (22–28 months old) and also bred in the same facility as young mice (2–3 months old). 20 In addition to a different antibiotic treatment, two different strains, VPI10463 and 630, were used to explore the impact of aging on CDI outcomes by infecting with strains of different virulence. 20 VPI10463, as described above, is a highly toxigenic strain that produces high levels of both toxin A and B, while 630, which is a clinical strain isolated from a patient, is considered low virulence due to the lower levels of toxin production.…”
Section: Antibiotic-induced Dysbiosis Aged Mouse Models Of CDImentioning
confidence: 99%